The Potential of Xanthones as a Therapeutic Option in Macrophage‑Associated Inflammatory Diseases - Ng, Ida May Jen; Chua, Caroline Lin Lin (Pharmacognosy Reviews)
Xanthones are well known for their significant biological activities and can be found in many herbal medicines. These compounds have the ability to regulate various inflammatory activities and signaling pathways in immune cells, especially macrophages. Macrophages are innate immune cells that can either fuel or dampen an inflammatory response depending on their activation states and play an active role in the development of inflammatory diseases such as atherosclerosis, arthritis, cancer, and diabetes. Many traditional medicines used as a remedy for these diseases contain xanthones, and their bioactivities may be partially attributed to their ability in regulating macrophage responses. In this review, we discuss the in vitro and in vivo findings on the effects of xanthones on different macrophage immune functions including nitric oxide and cytokine production, migration, polarization, and phagocytosis. Their specific modes of action are highlighted whenever known. We also discuss the potential and challenges in using xanthones as a therapeutic option in various inflammatory diseases. It is hoped that this review can pave the way for future research that focuses on developing xanthones as specific macrophage‑targeted therapeutics.
Keywords: Anti‑inflammatory; inflammation; macrophages; polarization; therapeutics; xanthones